Measurements of Periodic Signals Phase Shifts with Application of Direct Digital Synthesis - I. V. Gula; O. I. Polikarovskykh; K. I. Horiashchenko; I. V. Karpova; V. M. Melnychuk (Приборы и методы измерений)
The development of new methods and high-bit instruments for measuring phase shifts of high-frequency periodic signals with high speed for radar and radionavigation tasks is an actual task. The purpose of this work is to create a new phase shift meter for high-frequency periodic signals based on the double-matching method using direct digital frequency synthesis.On the basis of the proposed mathematical model of phase shift measurements of periodic signals by the method of double coincidence using the statistical accumulation of pulse coincidences, a functional diagram of a digital phase shift meter of periodic signals using a direct digital frequency synthesizer is developed. This allowed the implementation of an 8-bit converter phase shift signal to the code on the programmed logic integrated circuit EPM240T100C5N firm Altera.The digital phase shift meter of periodic signals based on the double-matching method consists of two comparators, two short-wave pulse generators, a direct digital frequency synthesizer, two pulse counter control circuits, two short pulse coincidence circuits, two pulse counting circuits, four clock counters, four registers, a microcontroller and an indicator. Block diagram of a double-matching digital phase meter using direct digital sintesizer use minimal hardware logic.In the developed phase shift meter, due to the use of the double-matching method, the time delay between signals does not depend on the period of input signals and can be found when changing the frequency of periodic pulses in wide limits. Measurement errors will be determined mainly by the duration of the pulses of coincidence. The use of statistical accumulation of pulse coincidence in the basis of the work allowed eliminating the restrictions on the duration of pulses of known non-ionic meters.On the basis of the obtained results, a high-bit converter of phase shifts of high-frequency periodic signals into a binary code with high speed for problems of industrial tomography, radar and radionavigation can be developed.